The Causes, Effects, and Determinants of the Farmers' Technical Efficiency in the Cassava Farms Affected by the Spilt Crude Oil in the Eneka Community in River State - Kalu, Victor Chiabuotu; OJimba, ThankGod Peter; Wilcox, Godwill Ibim; Obi, Raymond Chukwuemeka (Direct Research Journal of Agriculture and Food Science, 2024)
The study considered the causes, effects, and determinants of the farmers' technical efficiency in the cassava farms affected by the spilt crude oil in the Eneka community in Rivers State. A sample size of 48 respondents was selected using a multistage sampling procedure. Data were collected through scheduled interviews and observations using a structured questionnaire. The analysis used descriptive statistics and the Cobb-Douglas Stochastic Frontier Production Function. The study revealed that 79.17% of individuals involved in cassava production in crude oil spilt farms were males, while 20.83% were females. Additionally, more than 91% of the cassava farmers interviewed were under 60, with an average age of 47. Over 78% of the farmers were married. The majority of the sampled cassava farmers had an average farming experience of over 13 years and an average household size of 6 persons. The results of the Stochastic production function showed that technically inefficient variables of gender, education, marital status, household size, farming experience, labour, and farm size were statistically significant at 1%, in the area. Results further showed that crude oil spillage in the study area occurred because of sabotage (crude oil bunkering) (87.50%), giving rise to increased soil toxicity (97.92%), degradation of farmland, reduction of soil fertility (95.83%), low land productivity, decaying of tubers, poor yield, stunted growth, high level of food shortage, poor harvest and low income. This study concluded that crude oil spillage had detrimental and negative effects on cassava farms' quality of output, income, and the area of cropped farmland. Some recommendations were made, including immediate response to an oil spill, proactive measures in dealing with oil spillage, improving the security of various installations to prevent the vandalization of pipelines, and constant environmental monitoring and evaluation to determine the level of damage.
Keywords: Cassava farmers; crude oil; spillage; causes; effects; Eneka Community